Perbandingan Sistem Digitalisasi Lelang di Indonesia dan Korea Selatan: Dampak terhadap Efisiensi dan Transparansi - Dimas Dwi Putra; Ummi Maskanah; Febriana Miharja; Anggoro Nur Faqih (CV Rewang Rencang, 2025)
This research compares Indonesia's auction digitalization (lelang.go.id, LPSE) with South Korea's KONEPS using a comparative case study. It analyzes system architecture, regulations, and impacts on efficiency and transparency. The results show South Korea's KONEPS is superior: highly centralized, fully integrated (end-to-end), and supported by advanced technology (digital certificates, blockchain). Conversely, Indonesia, despite progress, faces system fragmentation between asset auctions and procurement, data interoperability issues, and uneven user adoption. South Korea's success lies in its single-window system integrity and strong political commitment, offering valuable lessons for Indonesia.